2023
DOI: 10.1021/acs.jpclett.3c00155
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Guest-Induced Structural Transitions in Metal–Organic-Framework MIL-53(Al)-NH2 Probed by High-Pressure Nuclear Magnetic Resonance

Abstract: A nuclear magnetic resonance (NMR) study of a pore opening in amino-functionalized metal−organic framework (MOF) MIL-53(Al) in response to methane pressure variation is presented. Variations of both NMR signal intensities and transversal relaxation rates for methane are found to reveal hysteretic structural transitions in the MOF material, which are smeared out over broad pressure ranges. Experiments with pressure reversals upon an incomplete adsorption/desorption gave deeper insight into the microscopic trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Universitetet i Oslo UiO-66 Zr (BDC) 1,4-benzenedicarboxylic acid [30][31][32] UiO-67 Zr (BPDC) biphenyl-4,4'dicarboxylate [30][31][32][33] UiO-68 Zr (TPDC) 1':4',1terphenyl-3,3'dicarboxylate [34][35][36] UiO-abdc Zr (abdc) (BDC-NH2) 2-amino-1,4benzenediacarboxylic acid [42,43] MIL-88B-Fe Fe (BDC) 1,4-benzenedicarboxylic acid [44] MIL-88B-4CH3 Fe (BDC-Me2) 2,5 dimethyl-1,4-benzenedicarboxylic acid [45] MIL-100-Fe Fe (BTC) benzene-1,3,5tricarboxylate [46,47] MIL-101 Cr (BDC) 1,4-benzenedicarboxylic acid [48] MIL-140 Ce (BDC) Solvothermal method, (4) Microwave method, (5) Sono-chemical synthesis method, (6) Electrochemical synthesis method, (7) Iono-thermal process method, (8) Mechanochemical method [71] .…”
Section: Uiomentioning
confidence: 99%
“…Universitetet i Oslo UiO-66 Zr (BDC) 1,4-benzenedicarboxylic acid [30][31][32] UiO-67 Zr (BPDC) biphenyl-4,4'dicarboxylate [30][31][32][33] UiO-68 Zr (TPDC) 1':4',1terphenyl-3,3'dicarboxylate [34][35][36] UiO-abdc Zr (abdc) (BDC-NH2) 2-amino-1,4benzenediacarboxylic acid [42,43] MIL-88B-Fe Fe (BDC) 1,4-benzenedicarboxylic acid [44] MIL-88B-4CH3 Fe (BDC-Me2) 2,5 dimethyl-1,4-benzenedicarboxylic acid [45] MIL-100-Fe Fe (BTC) benzene-1,3,5tricarboxylate [46,47] MIL-101 Cr (BDC) 1,4-benzenedicarboxylic acid [48] MIL-140 Ce (BDC) Solvothermal method, (4) Microwave method, (5) Sono-chemical synthesis method, (6) Electrochemical synthesis method, (7) Iono-thermal process method, (8) Mechanochemical method [71] .…”
Section: Uiomentioning
confidence: 99%
“…At room temperature, it undergoes a reversible transition from the large-pore to the narrow-pore phase through a breathing effect by adsorption of water molecules into the framework, ,, causing a significant volume fluctuation of up to 40%. This absorption-influenced transition is not limited to water alone, as other guest molecules, including CH 4 , N 2 , CO, and O 2 , have been shown to initiate a similar effect. Additionally, the stability of MIL-53­(Al) under high mechanical stress has also been noted, as it has been reported to undergo a pressure-induced phase transition from its large-pore form to the narrow-pore form at high pressures suggesting its suitability as a nanoshock absorber . Further, MIL-53­(Al) is environmentally and biologically friendly. Overall, the interesting guest-induced framework dynamics in MIL-53­(Al) are important to understand from a fundamental standpoint, in order to further design and tune the adsorption behavior of host–guest complexes, and this represents a model system for studying the broader class of flexible MOFs.…”
mentioning
confidence: 97%
“…This absorption-influenced transition is not limited to water alone, as other guest molecules, including CH 4 , N 2 , CO, and O 2 , have been shown to initiate a similar effect. 27 29 Additionally, the stability of MIL-53(Al) under high mechanical stress has also been noted, 30 as it has been reported to undergo a pressure-induced phase transition from its large-pore form to the narrow-pore form at high pressures suggesting its suitability as a nanoshock absorber. 23 Further, MIL-53(Al) is environmentally and biologically friendly.…”
mentioning
confidence: 99%
“…Owing to these merits, this technique has already been widely used in research and industry to study the fluid confined in porous media such as reservoir rocks, construction materials, and foods. ,, However, the traditional NMR relaxation theories for confined fluids may not apply to gas adsorption in a microporous material. It has been observed that the NMR relaxation times T 1 and T 2 of gas confined in micropores can be higher than the bulk phase, , which contradicts the traditional theories predicting that confined fluids always relax faster. , There is still a lack of a quantitative explicit model for NMR relaxation of gas adsorbed in microporous material, so although NMR relaxometry has been used to study the adsorption capacity, ,, molecular movement, and pore structure of multiple gas adsorption systems, the information that can be extracted from the results is limited.…”
mentioning
confidence: 99%